Estudo químico e farmacológico de plantas da caatinga: Cenostigma Pyramidale Gagnon & G.P.Lewis E Libidibia Ferrea LP Queiroz - Paiva, Cristiane Félix de (2021)
Medicinal plants are important sources of secondary metabolites, mainly used in the production of medicines. Many of these plants are used in traditional medicine by Brazilian communities in the treatment of various illnesses. A wide variety of medicinal plants occur in the Caatinga, and among these are Cenostigma pyramidale (Catingueira) and Libidibia ferrea (Pau-ferro). These species have great therapeutic and pharmacological potential due to their chemical composition, presenting compounds from the classes of flavonoids, tannins, organic acids, among other classes. This work aimed to carry out a pharmacological and chemical study of ethanol extracts from C. pyramidale bark and L. ferrea roots. In view of the large number of reports on the use of the species C. pyramidale, a literature search was carried out using the PubMed, Science Direct, Scopus and Web of Science tools, in search of its chemical composition, ethnopharmacological, pharmacological aspects and patentable potential. This research indicated that the flavonoid class is the most abundant, being found in the bark, leaves and roots of the species. Of these, agatisflavone, amentoflavone, podocarpusflavone, rhuschalcone VI and cesalpinioflavone revealed important pharmacological activities such as antiviral, antibacterial, neuroprotective, antioxidant, antiinflammatory and antiparasitic. In traditional medicine, this species is used for various purposes that are proven by its chemical composition and biopharmacological tests. The ethanol extract of the bark of C. pyramidale was submitted to tests to determine the antioxidant activity, the content of phenolic compounds and flavonoids, in addition to the anxiolytic potential against the zebrafish model (Danio rerio). The extract showed high free radical scavenging activity (IC50 = 6.397 ± 0.157 µg / mL) and content of phenolic compounds (71.4872 mg EAG / g of extract) and flavonoids (11.6803 mg EQuer / g of extract). The studied extract showed sedative and anxiolytic effects in the model used and did not show toxicity. The characterization of metabolites present in ethanol extracts from L. ferrea roots was performed by UPLC-ESI-QTOF-MS/MS and revealed the presence of flavonoids, organic acids and steroids in most of them. The root extract showed low content of phenolic compounds (31,189 ± 0.0176 mg / EAG.g-1) and low amount of flavonoids (3,148 ± 0.0014 EQuer / g of extract), good free radical scavenging with values of 9.8363 ± 0.5283 μg / mL for the DPPH radical and 14.0358 ± 0.0835 μg / mL for ABTS. The evaluation of cytotoxic activity was performed by MTT, the extract was active with 75% inhibition in two cell lines HCT-116 (human colon) and HL60 (Leukemia) with IC50 of 87.16 and 38.00 μg / mL, respectively. These results demonstrate that the species under study have biological potential and may be related to their metabolites. It is concluded that this study has an important contribution to the chemical and pharmacological knowledge of native Caatinga species.